SURVEY OF THE GUT PATHOGENIC MICROFLORA ASSOCIATED WITH CATERPILLARS OF THE BOX TREE MOTH CYDALIMA PERSPECTALIS WALKER, 1859 (LEPIDOPTERA: CRAMBIDAE) (Acta Entomologica Serbica, 2019)
The invasive box tree moth Cydalima perspectalis is an important and dangerous pest on Buxus spp. In this study, its destructive potential was evaluated in five areas of Bulgaria through the assessment of the defoliation levels caused by the caterpillars on the box trees. The microorganism species composition and diversity in the gut of caterpillars were investigated. In a total of 206 caterpillars, 5 bacterial (Acinetobacter schindleri, Enterococcus casseliflavus, Klebsiella mobilis, Paenibacillus anaericanus, and Paenibacillus popilliae) and 5 fungal species (Metarhizium sp., Beauveria sp., Verticillium sp., Alternaria sp. and Mucor sp.), were recovered. The most prevalent pathogen (52.4%) was the bacterium P. popilliae. Two entomopathogenic fungi, Metarhizium sp. and Beauveria sp., were observed in high and quite similar prevalences of 29.6% and 28.6%, respectively. The presence of these three pathogens (P. popilliae, Metarhizium sp. and Beauveria sp.) in relatively high levels in the gut of caterpillars indicates the possible role of gut pathogenic microorganisms as agents affecting caterpillar survival in natural populations of the pests. Further research is needed to assess the effect of the identified bacteria and fungi on C. perspectalis life stages.